Analisis Yuridis Tentang Perlindungan Hukum Bagi Ahli Waris Yang Tidak Hadir (Afwezig) Menurut KUHPerdata - Amelia, Meli; Wahyudi, Andri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The division of inheritance in Islam is a must. The distribution of property left by thedeceased is a manifestation of Islamic recognition of the existence of individual property rights. Individual property rights will end when a person dies, and transfers to the heirs. The process of implementing the property until it becomes an inheritancewhich will be distributed to the heirs, no one can postpone it. Since the determination of heirs to the part that must be obtained by each heir is a provision that must be implemented. The division of inheritance according to Islamic law is declared toexist, if the inheritance conditions are met. The fulfillment of the conditions of inheritance can entitle a person or heir to receive an inheritance. Between the conditions of "death of the heir" and the condition of "life of heirs" sometimes problems arise regarding inheritance issues, for example if someone dies leaving several heirs, and among the heirs there are people who are not present. People who are not present (afwezig) as legal subjects do not lose their rights in the distribution of inheritance. The purpose of this study is to find out how the concept of legalprotection for people who are absent (afwezig) in the distribution of inheritance according to the Civil Code is, and how the concept is implemented in society. The results of the study indicate that there is a concept of legal protection for absent heirs(afwezig) as regulated in Articles 490-492 of the Civil Code, namely the rights of absentees (afwezig) and their heirs cannot be eliminated. His right to inheritance will only be lost due to expiration. Legal protection for afwezig as heirs in the implementation of the distribution of inheritance in the community can only be carried out after a decision from the District Court stipulates that a person is not present.